Telesna dejavnost bolnikov z rakom debelega črevesa in danke - Zdešar, Tina (Šport (Ljubljana), 2016)
Colorectal cancer is a disease, characterized by high incidence rate and mortality. The most important etiological factors for the development of colorectal cancer are lifestyle related factors and genetic predispositions. Previous studies have shown the protective effects of regular physical activity that are more prominent in colon cancer than in rectal cancer. The primary purpose of this paper is to show the importance of regular physical activity in patients with colorectal cancer in terms of primary prevention as well as part of an overall treatment after diagnosis.
Keywords: cancer; dejavniki; factors; kakovost življenja; physical activity; physical fitness; rak debelega črevesa in danke; sport; šport; telesna dejavnost; vadba